Error-resilient packet-switched mobile video telephony with channel-adaptive rateless coding and early reference picture selection. Issue 6 (September 2016) - Dawood, Muneeb; Hamzaoui, Raouf; Ahmad, Shakeel; Al-Akaidi, Marwan
Abstract Providing high-quality video for packet-switched wireless video telephony on handheld devices is a challenging task due to packet loss, varying bandwidth, and end-to-end delay constraints. While many error resilience techniques have been proposed for video transmission over wireless channels, only a few were specifically designed for mobile video telephony. We propose a low-complexity channel-adaptive error resilience technique for packet-switched mobile video telephony, which combines rateless coding, feedback, and reference picture selection. In contrast to previous approaches, our technique uses cumulative feedback at every transmission opportunity and predicts when decoding is likely to fail so that reference picture selection can be triggered at an early stage. Experimental results for H.264 video sequences show that the proposed technique can achieve improvements of 1.64 dB in peak signal-to-noise ratio over benchmark techniques in simulated Long-Term Evolution networks.